(untitled) (Research, Society and Development, 2025)
Water, an essential natural resource for society, is widely used in various sectors, whether as a raw material in industrial processes, agriculture, leisure, the production of electronic components, cosmetics, and pharmaceuticals, or, primarily, for public supply. Its application is directly related to its quality and purity, determined by the treatment process to which it is subjected. In water treatment, chlorine is commonly used as an oxidizing and disinfectant agent, acting as a barrier against microbiological contamination. However, even in low concentrations, this chemical can be harmful to sensitive equipment, compromise the quality of end products through undesirable reactions, and, if discharged in high concentrations, be fatal to aquatic organisms, causing significant impacts to the ecosystem. Therefore, research into processes and technologies aimed at controlling and removing free residual chlorine is of great importance. As an alternative to conventional removal mechanisms, the photolysis process, based on exposure to ultraviolet radiation, is gaining prominence. This article presents a review on the use of photolysis in the removal of free chlorine from water, addressing the mechanisms involved in the reactions, the types of reactors and the main parameters that influence the process.